Tolvaptan as a tool in renal physiology - Miranda, Carlos A. (American Physiological Society, 2013)
For decades, the Brattleboro rat has been a useful model in kidney physiology. These animals manifest central diabetes insipidus (lack of circulating vasopressin) due to a mutation in the vasopressin-neurophysin gene. V2 receptor-mediated vasopressin actions in the kidney can be assessed in these animals by infusing the V2-selective vasopressin analog 1-desamino-8-d-arginine vasopressin (dDAVP). However, the major commercial supplier in the United States has ceased production, creating the need for another reliable experimental model of V2 receptor-mediated vasopressin action in rodents. We designed an in vivo protocol to investigate vasopressin responses in the rat kidney using osmotic minipumps loaded with tolvaptan, a nonpeptide competitive inhibitor of the vasopressin V2 receptor. Tolvaptan-infused rats had a mean urinary osmolality of <300 vs. >2,000 mosmol/kgH(2)O in vehicle-infused rats. The tolvaptan infusion produced large decreases in the renal abundance of aquaporin-2 (AQP2), aquaporin-3 (AQP3), the β-subunit of the epithelial sodium channel (β-ENaC), and γ-ENaC that were comparable to the differences seen in vehicle-infused vs. vasopressin-infused Brattleboro rats. Thus we conclude that tolvaptan infusion in rats provides an additional model (besides dDAVP-infusion in the Brattleboro rat) for the assessment of V2 receptor-mediated vasopressin actions in the kidney. We also provide ancillary in vitro data in rat inner-medullary-collecting-duct suspensions showing that tolvaptan can block vasopressin's effects on phosphorylation of the water channel AQP2 in vitro. Specifically, tolvaptan almost completely inhibited the ability of vasopressin to increase AQP2 phosphorylation at Ser256, Ser264, and Ser269, while strongly inhibiting a vasopressin-induced decrease in AQP2 phosphorylation at Ser261.